School drop out in Bangladesh: insights using panel data - Sabatés, Ricardo; Hossain, Altaf; Lewin, Keith M. (© 2012 Elsevier Ltd., 2016)
This article was published in the International Journal of Educational Development [© 2012 Elsevier Ltd.] and the definite version is available at : http://doi.org/10.1016/j.ijedudev.2012.09.007. The Journal's website is at:http://www.sciencedirect.com/science/article/pii/S0738059312001228